A Reflection of the Position that Social Work Played in Tackling Coronavirus in South Africa - Simon Murote Kang’ethe (E-Journal of Humanities, Arts and Social Sciences)
Inopportunely, the coronavirus in the 20-21 epoch ubiquitously overwhelmed many countries around the globe, and those in Africa begging for interventions to surmount the quagmire. This article aims to reflect on how social work played a role in tackling the quagmire of coronavirus in the 2020-2021 coronavirus epoch in South Africa. The paper applied a literature review methodology by drawing data from twenty English-authored articles from various Google search engines such as Google Scholar, EBSCOhost, Research Gate, monographs, books, and book chapters. This researcher thinks that social workers during the COVID era achieved the following: Fighting coronavirus-driven poverty, facilitating psychosocial therapeutic interventions, such as counseling to the victims of gender-based violence, mobilized communities to embrace the spirit of Ubuntu, and offering caregiving to those infected. This role, this researcher believes, unequivocally mitigated the impact of the disease and assisted in raising the societies’ preparedness to handle the coronavirus pandemic astutely. The article recommends that government, NGOs, and philanthropic bodies collaboratively empower social workers in their social welfare interventions to face pandemics such as coronavirus. Societies have also been implored to embrace the spirit of Ubuntuism to strengthen their caregiving norms and spirit. The article generates knowledge that social workers will use to intervene in the event of coronavirus coming back or in any future pandemic. This article broadens the research horizon in pandemics such as coronaviruses and those that will come in the future.